Efeito da fadiga induzida por séries múltiplas no défict muscular de individuos treinados e menos treinados - Fortes, Emmanuel Nunes Silva (2019)
The aim of this study was to verify the influence of multiple bench press series on muscle deficit kinetic parameters of trained and less trained young people. The sample comprised 49 university students divided into two groups: trained and less trained according to the training time. Data collection was divided into two sessions; in the first session the volunteers were familiarized with the protocol for the evaluation of maximal isometric elbow flexion and extension voluntary contractions. Then, the protocol proposed by Brizcky was performed, in which the maximum strength was determined by means of the 1-RM test in the bench press bench press. The start of testing was preceded by a warm-up series (six to 10 repetitions) with approximately 50% of the estimated load for the first attempt on the 1-RM test. After two minutes of rest the test was started. Subjects were instructed to try to complete two repetitions. If the two repetitions were completed on the first attempt, or even if not a single repetition was completed, a second attempt was made after a recovery interval of three to five minutes with a higher load. The load recorded as 1-RM was that in which each individual was able to complete a single maximum repetition. The second session was intended for the assessment of volunteers by the MVIC and induction of fatigue from multiple series with the load measured in the first session by the protocol proposed by Brizcky, with an interval of one week between sessions. MVIC was measured before and immediately after fatigue induction. Still, anthropometric measurements such as weight and height were evaluated. From the MVIC that presented the highest peak force, the following variables were calculated: Force Production Rate (TPF), Peak Force (PF), Average Force (FMÉD). The sample was characterized by calculating mean, standard deviation and effect size by Cohen. Statistical tests such as ShapiroWilk, T-test for paired samples, T-test for independent samples and mixed two-way ANOVA (group x moment) were applied according to the variables studied. The mean and standard deviation were statistically higher among the trained for several variables, representing greater strength among the trained. There were no significant differences between groups for the variations of the variables analyzed from the peak force. The least trained group had lower performance variation compared to the trained group for the mean right elbow extension strength variables; mean force of left elbow extension; mean right elbow flexion strength. Differences between groups were observed for variations in left elbow extension force production rate (p = 0.01), right elbow flexion force production rate (p = 0.03), left elbow flexion strength production (p = 0.04), right elbow triceps / biceps ratio (p = 0.01), elbow extension asymmetry index (p = 0.03). For the triceps / biceps ratio, significant differences were found for both upper limbs in the dynamic variables: mean strength and strength production rate. The results partially refute the third hypothesis of the present study which would be that a more trained individual would present a lower reduction of the biceps brachii performance thus causing a smaller and significant T / B ratio when compared to the less trained individual. It can be concluded that the experimental protocol for upper limb fatigue induction of active individuals composed of multiple series was able to reduce the performance, that the applied fatigue protocol was not able to generate different effects on the upper limbs according to the level of training.